2008
DOI: 10.1074/jbc.m709299200
|View full text |Cite
|
Sign up to set email alerts
|

HtrA1 Inhibits Mineral Deposition by Osteoblasts

Abstract: HtrA1 is a secreted multidomain protein with serine protease activity. In light of increasing evidence implicating this protein in the regulation of skeletal development and pathology, we investigated the role of HtrA1 in osteoblast mineralization and identified domains essential for this activity. We demonstrate increased HtrA1 expression in differentiating 2T3 osteoblasts prior to the appearance of mineralization. HtrA1 is subsequently down-regulated in fully mineralized cultures. The functional role of HtrA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…This enzyme, high-temperature requirement factor A1 (HtrA1) is a secreted serine protease that degrades several matrix components including decorin, fibronectin, aggrecan, type II collagen 30,31 and impairs elastogenesis by cleaving fibulin 5 30 . Interestingly, while HtrA1 protein levels were increased in smLRP1-/- aortic extracts, mRNA levels for htra1 were not altered in these mice (Fig 4b).…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme, high-temperature requirement factor A1 (HtrA1) is a secreted serine protease that degrades several matrix components including decorin, fibronectin, aggrecan, type II collagen 30,31 and impairs elastogenesis by cleaving fibulin 5 30 . Interestingly, while HtrA1 protein levels were increased in smLRP1-/- aortic extracts, mRNA levels for htra1 were not altered in these mice (Fig 4b).…”
Section: Resultsmentioning
confidence: 99%
“…However, it wasn’t until several years later that evidence emerged of a possible functional role for HTRA1 in bone formation. Studies performed using mouse-derived osteoblasts demonstrated that despite its upregulation in response to BMP-2, HTRA1 acted as a negative regulator of bone formation [29, 30]. Moreover, the observation that Htra1 -deficient mice have a moderately improved bone phenotype [31], suggested that HTRA1’s influence on bone may go beyond simply affecting mineral formation in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, HTRA1 protein has been detected in developing bones in vivo , as well as in fracture callus [9, 15, 19]. However, in contrast to these findings, several studies now exist in which HTRA1 has been demonstrated to impart a negative influence over osteogenesis [29, 30]. Although the cause of these conflicting results remains unclear, it is important to note that inherent differences exist between the cell culture systems used in each of these studies, and may therefore indicate that cell specific effects of HTRA1 need to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…29 The N- and C-terminal domains of HtrA1 comprise an IGFBP-like/Kazal-like tandem domain motif (termed the N-domain) and a PDZ domain, respectively. Both seem largely dispensable for catalytic function, 30 and whereas the PDZ domain facilitates protein–protein interactions by tethering of the HtrA1 protease to specific sites in the ECM or in the cell, 4,26,31 the role of the N-domain remains enigmatic. The domain contains a total of 16 cysteines, all forming part of an intensive disulfide bond network (Figure 1).…”
mentioning
confidence: 99%